Long Chain Fatty Acid Degradation Coupled to Biological Sulfidogenesis: A Prospect for Enhanced Metal Recovery - Florentino, Anna Patrícya; Costa, Rachel Biancalana; Hu, Yuansheng; O'Flaherty, Vincent; Lens, Piet N. L. (Frontiers in Bioengineering and Biotechnology, 2020)
This research assessed the microbiological suitability of oleate degradation coupled to sulfidogenesis by enriching communities from anaerobic sludge treating dairy products with S0, SO32-, SO42- and S2O32- as electron acceptors. The limiting factor hampering highly efficient oleate degradation was investigated in batch reactors. The best sulfidogenic performance coupled to specialization of the enriched bacterial community was obtained for S0- and S2O32--reducing enrichments, with 15.60 (± 017) and 8.99 (± 0.02) mM of sulfide production, respectively. Microbial community analyses revealed predominance of Enterobacteraceae (50.60 ± 5.66%), Sulfurospirillum (23.10 ± 0.14%), Bacteroides (7.45 ± 1.48%) and Seleniivibrio (6.95 ± 1.06%) in S0-reducing cultures. In S2O32--reducing enrichments, the genus Desulfurella predominated (49.25 ±1.20%), followed by the Enterobacterales order (20.90 ±2.26%). S0-reducing cultures were not affected by oleate concentrations up to 5 mM, while S2O32--reducing cultures could degrade oleate in concentrations up to 10 mM, with no significant impact on sulfidogenesis. In sequencing batch reactors operated with sulfide stripping, the S0-reducing enrichment produced 145.84 mM sulfide, precipitating Zn as ZnS in a separate tank. The S2O32- fed bioreactor only produced 23.42 mM of sulfide precipitated as ZnS. The lower sulfide production likely happened due to sulfite toxicity, an intermediate of thiosulfate reduction. Therefore, elemental sulfur reduction represents an excellent alternative to the currently adopted approaches for LCFA degradation. To the best of our knowledge, this is the first report of oleate degradation with the flux of electrons totally diverted towards sulfide production for metal precipitation, showing great efficiency of LCFA degradation coupled to high levels of metals precipitated as metal sulfide.